Thoracic endovascular aortic repair for recurrent stroke due to atheromatic plaque in the proximal descending aorta: a case report - Masafumi Hashimoto; Yoshikazu Nakano; Yusaku Tamura (Surgical Case Reports, 2021)
Abstract Background Diastolic retrograde flow in the descending aorta (DAo) may occur in the presence of atherosclerosis and may be overlooked as a mechanism of retrograde embolization in patients with stroke. We performed thoracic endovascular aortic repair (TEVAR) in a patient with recurrent cerebral infarctions for treatment of aortic aneurysm with atheromatic plaque, which was considered as the source of embolism. Case presentation A 56-year-old man with a history of idiopathic thrombocytopenia and hypertension was referred to our hospital with paralysis of the right upper and lower limbs. Multiple cerebral infarctions were found and treated; however, 1 month later, another cerebral infarction developed. A small saccular aortic aneurysm with plaque was found beyond the left subclavian artery, and this site was deemed as the source of embolism. We performed TEVAR to prevent further recurrence of cerebral infarctions. No cerebral infarctions were observed 6 months post-operation. Conclusions TEVAR is a useful treatment for not only aortic aneurysm and dissection, but also cerebral infarctions caused by an embolic source proximal to the DAo due to retrograde aortic blood flow.